Woman’s Way to Academia: Past and Present - Žvinklienė, Rūta (Sociologija. Mintis ir veiksmas, 2003)
The main idea of the article to show that the practice oflegal “equal rights” even enlarged by concept of “equal opportunities” entails more dissembled and sophisticated forms of women’s discrimination, and therefore gender has remained under the control of public discourse.In spite of society’s democratisation, the development of gender ideology remained in the frame of Chistian structure: a woman is a servant of a man. Women on the top of social hierarchy, regardless of positive changes towards women’s representation here, were, and are rather an exception than a rule. Sociological analysis of this social phenomenon is based on case study of women in science in Lithuania from a historical-cultural perspective and recent qualitative research data on academic women. Academic women indicate women who are teaching and/or pursuing scientific research in universities and/or scientific research institutions.Social history may be regarded as a permanent struggle between woman’s exclusion from the so-called public sphere by pushing her towards a private sphere on the one hand, and woman’s strife for inclusion in the public sphere on another hand. The main instrument of this struggle is access to education. Social factors influencing the number of women in science are the public attitudes concerning the standard of sufficient education for a woman, and how science - its branches, its specialization, namely research and/or teaching - is associated with a female carrier.Despite the trend towards the so-called feminization of definite disciplines, mostly in humanities and social sciences that has a long historical tradition, science is after all a highly masculine activity also, with still visible divisions between masters and servants from a gender perspective. The leadership in academy remains in the frame of the “old boys network”, and the most academic women remain slaves of gender that precludes them from leadership in academy as well. Slaves of gender means that women prefer/are compelled to follow traditional gender patterns that prescribe them main duties in the private sphere.Solution of socialistic “Women’s question”, that is implementation of the principle of equality between women and men does not achievement of the last generation. The equal rights of individual choice to vote, education, profession, etc. are executed by several generations of Lithuanians, and hence, became an inherent part of the public discourse. That is why the fact of informal women’s discrimination is often perceived as a norm of existing culture or at least non- actual social issues.
Keywords: rights; discrimination; academia